Temporal analysis of land use in Guajará, Amazonas, Brazil - Anjos, Kelyan Lago dos; Almeida Filho, Luciomar da Silva (Revista Cerrados, 2024)
Environmental degradation in the Amazon is a recurring theme in environmental management and geography studies, especially when the focus is turned to analyzing agricultural production and its continuous association with deforestation. The purpose of this study is to analyze land use and land cover in the municipality of Guajará, Amazonas between 1985 and 2022, in order to verify the growth dynamics of the area used for anthropogenic purposes using data from the 1995-1996 and 2006 IBGE agricultural censuses and the MAPBIOMAS project. The methodology is based on the theoretical framework and consists of processing and mapping the MAPBIOMAS use classes and statistical processing of the agricultural census data. The result shows a significant increase in the area of the pasture class, in two axes of growth to the southern portion of the municipality, due to its strong economic relationship with the state of Acre